PENERAPAN PSAK NO.45 TENTANG PELAPORAN KEUANGAN ORGANISASI NIRLABA YAYASAN PENDIDIKAN PONDOK PESANTREN AL-KHAIRIYAH - Atufah, Intan Devi (Universitas Pendidikan Ganesha, 2018)
Now days non profit organizations in Indonesia still tend to emphasize the priority of program quality and not too much attention to the importance of financial management systems. Though a good financial management system is believed to be one of the main indicators of accountability and tranparency of an institution. Reporting and financial management of the corresponding set in the Statement of Financial Accounting Standards (SFAS) 45 of the financial reporting of nonprofit organizations. The purpose of this study was to determine whether application of the financial reporting on Educational Foundation Boarding School Al-Khairiyah with what has been stated in SFAS 45. Descriptive research methods with qualityve analysis techniques outlines, describe and recontruct a data. The result showed that the financial statement in accordance with the Educational Foundation Boarding School Al-Khairiyah yet financial statement based nonprofit financial statement formats that exist in SFAS 45. The financial statements of which there are some cash flow statements regarding expenditures and income to their understanding. Educational Foundation Boarding School Al-Khairiyah does not present a statement of financial position, statement of activities, statementof cash flows, and notes to the financial statements. The preparation of financial statement sshould be guided by Educational Foundation Boarding School Al-Khairiyah and follow the conditions set by the Indonesian Institute of Accountants (IAI) contained in SFAS 45 that the information presented in the financial statement be clear, relevant and has a high appeal